1977
DOI: 10.1159/000119668
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Arterial Aneurysms in Infancy and Childhood

Abstract: Eleven cases of intracranial arterial aneurysms in patients under 15 years of age, treated from 1959 to 1976, are presented. The preponderance of aneurysms at the internal carotid artery bifurcation and the peculiarities of the defects in this location are remarkable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 8 publications
2
19
0
2
Order By: Relevance
“…In the present series, there were 16 cases of SAH and only 1 case of intraventricular bleed secondary to aneurysm. Anatomic localization at the internal carotid bifurcation is a distinguishing feature of aneurysm affecting children and adolescents [33, 35, 36]. In the present series, too, ICA bifurcation was the most common site of aneurysms (27.8%), followed by MCA (22.2%) and anterior communicating artery aneurysm (16.7%).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In the present series, there were 16 cases of SAH and only 1 case of intraventricular bleed secondary to aneurysm. Anatomic localization at the internal carotid bifurcation is a distinguishing feature of aneurysm affecting children and adolescents [33, 35, 36]. In the present series, too, ICA bifurcation was the most common site of aneurysms (27.8%), followed by MCA (22.2%) and anterior communicating artery aneurysm (16.7%).…”
Section: Discussionmentioning
confidence: 47%
“…Intracranial aneurysms have been found to have a sex predilection for young boys compared to girls with an approximate ratio of 1.8:1 [33, 34]. Aneurysms in pediatric populations are more likely to present with SAH [33, 35, 36]. In the present series, there were 16 cases of SAH and only 1 case of intraventricular bleed secondary to aneurysm.…”
Section: Discussionmentioning
confidence: 67%
“…The most common presentation of intracranial aneurysms in children is subarachnoid hemorrhage [10,15,17]. Presentation secondary to mass effect (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…There is a higher incidence of giant aneurysms (12.5 cm) in children compared to adults [10,15,19]. In addition, aneurysms in children are more likely to occur at the internal carotid bifurcation [17,20,21] or the posterior circulation [15,19,21]. However, some authors have found these aneurysms to be more peripherally located [10,22].…”
Section: Discussionmentioning
confidence: 99%
“…As well, traumatic intracranial aneu rysms are recognized to be rare, comprising less than 0.5% of all intracranial aneurysms in a large hospital series spanning roughly 20 years [4], However, roughly one fourth of the reported traumatic aneurysms have involved pediatric patients [5]. Such numbers indicate that either traumatic intracranial aneurysms are more common in the pediatric versus the adult population [3,6] or that some bias exists for reporting such aneurysms in children as compared to adults. A comprehensive review of the lit erature in 1988 revealed 69 well-documented cases of traumatic intracranial aneurysms in childhood, with an overall mortality rate of 31%, but with roughly 2/3 of all operated cases resulting in a good or excellent outcome [7], Since that time several additional papers concerning traumatic intracranial aneurysms have been published …”
Section: Introductionmentioning
confidence: 99%